Pub art - Keratová, Mira; Ročkárová, Zita (Slovart, 2017)
"Pub art" is a selection of free drawings by Cyril Blazo and Martin Kochan, created jointly in recent years in pubs and bars mainly in Trnava, where Kochan lives and Blazo, his former tutor teaches at Trnava university. The pub art drawings, initially caricatures, came about by a spontaneous chain sketching of their shared ideas. Often they derived from authentic themes of the pub setting
Keywords: Kochan, Martin -- 1981-; Blažo, Cyril -- 1970-; Bildband